2014
DOI: 10.1016/j.jmaa.2013.08.069
|View full text |Cite|
|
Sign up to set email alerts
|

Sobolev estimates for averaging operators over a convex hypersurface in R3

Abstract: We prove sharp L p -Sobolev estimates for averaging operators associated with a certain type of convex hypersurface in R 3 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…To prove Proposition 1.1 in [3], we used Lemma 6.2 together with van der Corput lemma. But we have found that there are technical errors in (6, 9) and (6, 10) of Proposition 1.1.…”
Section: Statements Of Proposition 11 and Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…To prove Proposition 1.1 in [3], we used Lemma 6.2 together with van der Corput lemma. But we have found that there are technical errors in (6, 9) and (6, 10) of Proposition 1.1.…”
Section: Statements Of Proposition 11 and Preliminariesmentioning
confidence: 99%
“…But we have found that there are technical errors in (6, 9) and (6, 10) of Proposition 1.1. To correct these errors, we replace Lemma 6.2 in [3] by Lemma 1.1. Let a, b and M be positive even integers satisfying a 2 + b M ≥ 1, and let Φ be a function of the form…”
Section: Statements Of Proposition 11 and Preliminariesmentioning
confidence: 99%